Studies on the Nature of Antihemophilic Factor (Factor VIII): FURTHER EVIDENCE RELATING THE AHF-LIKE ANTIGENS IN NORMAL AND HEMOPHILIC PLASMAS - Bennett, Bruce (1973)
Normal human antihemophilic factor (AHF, factor VIII) and the protein antigenically related to it in hemophilic plasma both appeared in the void volume of columns of agarose (Sepharose 4B) during purification of these agents. On ultracentrifugation upon sucrose gradients, both agents had sedimentation characteristics similar to those of an S30 marker. After reduction, the polypeptide chains of purified normal AHF and of the nonfunctional agent from hemophilic patients had an apparent molecular weight of 200,000 as determined by sodium dodecyl sulfate polyacrylamide gel electrophoresis. These observations suggest that AHF, purified as described, exists as a large molecule with subunits of molecular weight of approximately 200,000. Antisera to normal AHF and the nonfunctional agent from hemophilic plasma appeared to be directed against antigens of similar electrophoretic mobility and precipitating characteristics, present in normal and hemophilic plasma but deficient in severe von Willebrand's disease plasma. Both antisera neutralized the AHF clot-promoting activity present in normal plasma, and this property was removed by absorption of the antisera with concentrates of normal or hemophilic plasma but to a greatly reduced extent by concentrates of von Willebrand's disease plasma. These findings suggest that the antigen detected in normal plasma by the antisera appears on a molecule participating in the AHF clot-promoting reaction.